A galvanic replacement-based Cu2O self-templating strategy for the synthesis and application of Cu2O–Ag heterostructures and monometallic (Ag) and bimetallic (Au–Ag) hollow mesocages12. Issue 12 (8th March 2017) - Bakthavatsalam, Rangarajan; Kundu, Janardan
Abstract : Galvanic replacement based self-templating strategy has been well-demonstrated for controlled fabrication of octahedral Cu2 O–Ag heterostructures and octahedral hollow Ag mesocages utilizing charged surfactant. Abstract : Polyhedral Cu2 O microparticles as self-templates have been well-demonstrated for the synthesis of Cu2 O–M heterostructures (M = Au, Pd, Pt) and Au nano/mesocages utilizing the galvanic replacement reaction (GRR) strategy. However, reports on GRR-based fabrication of Cu2 O–Ag heterostructures and the ensuing Ag mesocages are scanty. There is no report that describes the phenomenon of facet selectivity during the GRR-based deposition of Ag on Cu2 O template particles. Here, we have identified the underlying rationale behind the observed difficulty in nucleating Ag nanoparticles on an octahedral Cu2 O self-template particle. Utilization of an appropriately chosen surfactant/complexant for the silver precursor helps in demonstrating the successful fabrication of Cu2 O–Ag heterostructures (octahedral, cubic) with a tunable loading density of Ag NPs on the Cu2 O surfaces. This is achieved using Cu2 O template particles that undergo GRR with silver nitrate in the presence of nitric acid, and 5-sulfosalicylic acid as the surfactant (key role players). We provide evidence that supports facet selectivity during the deposition of Ag NPs on Cu2 O cuboctahedral particles. Hollow octahedral Ag and Au–Ag bimetallic mesocages are fabricated that have rough surfaces, uniform morphology, and excellent shape retention. The fabricated heterostructures and mesocages act as an excellent SERS substrate. This is the first report on the rational synthesis of octahedral Cu2 O–Ag heterostructures and octahedral hollow metallic mesocages utilizing the Cu2 O self-templating strategy along with the demonstration of facet selectivity of Ag deposition on Cu2 O template particles through GRR. The current approach offers a facile and versatile protocol for the synthesis of Cu2 O–metal heterostructures and hollow noble metal mesocages.